UJI BEBERAPA MEDIA TANAM TERHADAP PERTUMBUHAN STEK TRUBUSAN DARI TUNGGUL SISA PENEBANGAN Eucalyptus pellita - Azis Gunawan; M. Mardhiansyah; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The needs of wood as a main ingredient of paper is constantly increasing. To overcome its problem one of the alternative solution is  Industrial Plantation  Forest  (HTI). Eucalyptus pellita is one of the type which is developed for HTI that is necessary to be provided adequate and quality seeds, it is necessary to propagation the plant of Eucalyptus pellita. Stump out of the wood Eucalyptus pellita can produce the new coppice that can produce seed plants and can be developed by propagation of plants as vegetative by cuttings. One of the factors that affect the success rate of cuttings is the planting media. The problem is what is the proper planting media in developing the growth of coppice cuttings from the stump of the wood Eucalyptus pellita. The purpose of this study is to determine the appropriate planting media to be used on coppice cuttings from the rest of the harvest Eucalyptus pellita. The method used in this study is Completely Randomized Design (CRD). The results showed that the use of planting media peat or compost and rice husk or compost and rice husk with a ratio of 3:1 and 1:1 as well as the addition of coconut fiber powder at the top of the media can be used as a planting medium coppice cuttings from stump rest of logging Eucalyptus pellita. Keywords: coppice, cuttings, planting media, Eucalyptus pellita